Selection of papers presented at the symposium MPLP-2018 : Vertical-cavity surface-emitting lasers with intracavity contacts and a rhomboidal current aperture for compact atomic clocks. (14th February 2019) - Blokhin, S A; Maleev, N A; Bobrov, M A; Kuz'menkov, A G; Vasil'ev, A P; Zadiranov, Yu M; Kulagina, M M; Blokhin, A A; Guseva, Yu A; Ospennikov, A M; Petrenko, M V; Gladyshev, A G; et al.
Abstract: Single-mode vertical-cavity surface-emitting lasers (VCSELs) with intracavity contacts, composite distributed Bragg reflectors, and a rhomboidal selectively-oxidised current aperture are studied. It is shown that the use of a rhomboidal current aperture allows the light output polarisation to be fixed without using a special surface relief and leads to efficient narrowing of the emission line with retaining a high slope efficiency. The developed VCSELs have a high output power (exceeding 1 mW), a threshold current below 1 mA, an effective modulation frequency exceeding 5 GHz, and a linewidth smaller than 60 MHz at increased (65–75 °C) temperatures and are promising for application in compact Cs vapour cell atomic clocks.